Analysis of Indonesia Business Cycle through Composite Leading Indicator Data Processing for Banking Industry - Riwi Sumantyo; Annisa Wahyuningsih (University of Merdeka Malang, 2017)
This study aimed to analyze the business cycle of Indonesia through data processing CLI (Composite Leading Indicator) and to obtain an investment leading indicator which a composite of several indicators. This study used the OECD method and used time series data, i.e. quarterly data from 2001-2013. The result of the analysis of this study was the formed CLI was well functioned (significant), although the correlation coefficient both not overlapped (low). Because the IDX Composite movement was more volatile than GDP movement. However, the formed CLI was capable in following the cyclical movement of the reference series (significant). The result of hypotheses in this study was assumed that there were some variables that met the category as a leading indicator in GDP reference series that were: CPI, exchange rate, property credit, and housing loan. While the variables in the reference series IDX composite namely: import capital, Pi_paper, export manufacture, export agriculture, housing loan, and property credit. In this study, especially for the government and central bank (Bank of Indonesia), they should be able to work together in making policies that pay attention to the economic variables classified in leading indicators. DOI: https://doi.org/10.26905/jkdp.v21i4.1553